Idiopathic ascites following caesarean section: A case report - Tate, Jessica; McGrath, Niamh; Lalchandani, Savita (Clinical Journal of Obstetrics and Gynecology, 2023)
Ms X is a 40-year-old gravida 12, para 2 + 9 woman, who was admitted for an elective caesarean section at 38 weeks gestation following the previous two caesarean sections. Ms X had abdominal distension and generalised abdominal tenderness in the postoperative period. On investigation, she was found to have an elevated white cell count (WCC), C - Reactive Protein (CRP) and creatinine with free fluid in the abdomen on imaging but there was no evidence of perforation of any visceral organ. Ms X was treated conservatively for sepsis, an Acute Kidney Injury (AKI) and post-operative ileus and her symptoms gradually resolved. This is a case of idiopathic ascites post caesarean delivery with no clear cause.